2021
DOI: 10.1186/s12936-021-03840-w
|View full text |Cite
|
Sign up to set email alerts
|

Socio-economic and household determinants of malaria in adults aged 45 and above: analysis of longitudinal ageing survey in India, 2017–2018

Abstract: Background Even though malaria cases have drastically come down in the last decade, malaria remains a serious public health concern in many parts of India. National Framework for Malaria Elimination in India (2016–2030) has been launched with the goal to eliminate malaria by 2030. Understanding the socio-economic and household determinants of malaria at the national level will greatly aid India’s malaria elimination efforts. Methods The data from L… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
5
4
0
Order By: Relevance
“…Although smoke from biomass cooking is often associated with reduced mosquito abundance and malaria transmission [ 44 ], the results of this study indicated that households which used firewood and straw for cooking were more likely to have their children contracting malaria compared to households which used charcoal. This result is consistent with other studies [ 45 ]. There are potential reasons to this finding.…”
Section: Discussionsupporting
confidence: 94%
“…Although smoke from biomass cooking is often associated with reduced mosquito abundance and malaria transmission [ 44 ], the results of this study indicated that households which used firewood and straw for cooking were more likely to have their children contracting malaria compared to households which used charcoal. This result is consistent with other studies [ 45 ]. There are potential reasons to this finding.…”
Section: Discussionsupporting
confidence: 94%
“…Although smoke from biomass cooking is often associated with reduced mosquito abundance and malaria transmission (50), the results of this study indicated that households which used rewood and straw for cooking were more likely to have their children contracting malaria compared to households which used charcoal. This result is consistent with other studies (51). There are potential reasons to this nding.…”
Section: Discussionsupporting
confidence: 94%
“…The endophagic behavior of the mosquitos can also explain the impact of open eaves, which was associated with increased risk of infection. Prevalence was also higher among males, in school age children, and in households where the head had not completed secondary school, corroborating previous findings [64][65][66][67][68][69].…”
Section: Discussionsupporting
confidence: 89%